(untitled) (Architecture Image Studies, 2026)
Increasing frequency and intensity of storms, driven by climate change, present significant challenges to architectural resilience in vulnerable regions. Adaptive design strategies, which integrate risk-informed architectural responses, have become essential for reducing structural and social vulnerability. This research focuses on evaluating climate risk impacts on the built environment and formulating adaptive design approaches for storm resilience. The primary objective is to identify architectural modifications that enhance safety, durability, and functional continuity during extreme weather events. Data collection involved semi-structured interviews with 245 local residents in storm-prone coastal areas to understand practical adaptation strategies and community-level perceptions of structural vulnerability. Analysis employed a mixed-methods approach, combining qualitative thematic coding of interview responses with quantitative assessment of structural and environmental risk indicators. Key metrics included material durability (MD), Roof reinforcement effectiveness (RRE), Wall reinforcement effectiveness (WRE), spatial layout effectiveness (SLE), and drainage efficiency (DE). Correlation and regression tests were conducted using SPSS to evaluate relationships between climate exposure variables and architectural adaptation measures. Results reveal that adaptive architectural strategies, including storm-resistant materials, significantly enhance storm resilience. T-tests show higher mean scores for adaptive measures (SLE: 4.1, DE: 4.2) compared to traditional designs. Chi-Square and Analysis of Variance (ANOVA) confirm significant differences, while multiple regression and correlation analyses highlight RRE, DE, and SLE as key predictors, emphasizing spatial layout, drainage efficiency, and storm-resistant materials in reducing vulnerability. In conclusion, the research underscores the value of combining empirical climate data, architectural assessment, and community experience to formulate practical adaptive design strategies.